Automation system of table tennis ball throwing machine employing arduino microcontroller - Rassad, Pikrur; Sukardi (Department of Electrical Engineering Universitas Negeri Padang, 2024)
Table tennis is one sport that necessitates the usage of automation technologies. A microcontroller running Arduino programming software serves as the foundation for this table tennis ball tossing apparatus. A straightforward tool that helps coaches and athletes be more efficient. A different tool design model is what the author desires. Equipment for tossing table tennis balls is still quite hard to come by in Sumatra, particularly in the West. The created tool is utilized in the training procedure for tennis balls. In West Sumatra, tennis instruction is typically conducted by hand. Athletes can move by throwing the ball one at a time. It is less efficient to do this. Coaches and sportsmen may find it more convenient if table tennis ball throwing equipment are automated. This instrument takes the shape of a ball that can be controlled with a Bluetooth switch. Training for table tennis is no longer done by hand thanks to this tool